ANALISIS KEMAMPUAN BERFIKIR KRITIS DALAM KEGIATAN BELAJAR MENGAJAR PENDIDIKAN AGAMA ISLAM BERDIFERENSIASI METODE GALLERY WALK PADA SISWA SEKOLAH PERTAMA NEGERI 30 KABUPATEN MUARO JAMBI - Shamila Aisah Ayu; Sukarno; Samsu (STKIP Subang, 2026)
This research was motivated by the low critical thinking skills of class VII A students in the subject of Islamic Religious Education and Character Education at Junior High School 30 Muaro Jambi Regency. The low level of critical thinking skills was indicated by students’ lack of ability to analyze learning materials, express opinions, provide logical reasons for their answers, and solve problems related to the lesson material. Therefore, an appropriate learning method is needed to improve students’ critical thinking skills, one of which is differentiated learning through the Gallery Walk method. This study aims to analyze students’ critical thinking skills in the teaching and learning process of Islamic Religious Education through differentiated learning using the Gallery Walk method for class VII A students at Junior High School 30 Muaro Jambi Regency. This research used a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects consisted of Islamic Religious Education teachers and class VII A students. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study showed that the implementation of differentiated learning using the Gallery Walk method was able to improve students’ critical thinking skills. This could be seen from the increased ability of students to ask questions, provide responses, analyze learning materials, participate in discussions, express logical opinions, and collaborate in groups to complete learning tasks. In addition, differentiated learning helped teachers adjust learning strategies according to students’ characteristics and learning needs, making the learning process more active, interactive, and meaningful. Supporting factors in implementing this method included teacher creativity, student cooperation, and a conducive learning environment, while the inhibiting factors included limited learning time and differences in students’ levels of understanding of the material. Keywords: Critical Thinking Skills, Differentiated Learning, Gallery Walk Method, Islamic Religious Education and Character Education.